Experimental investigation of a novel walking stick in avoidance drop-off for visually impaired people. Issue 1 (1st January 2019) - Billah, Md Masum; Mohd Yusof, Zulkhairi; Kadir, Kushsairy; Mohd Ali, Abdul Malik; Nasir, Haidawati; Sunni, Amirul
Abstract: Blindness happens from the visual impairments of a person either naturally or accidentally. Usually, blind people used to move along with a white cane. Visually impaired people completely depend on it where they move with the cane in front of them to check obstacle during their mobilization. However, one of the most common problems found these people usually fall or drop off in the front hole or drain. Moreover, blindness makes people veering during their movement thus they could not detect the narrow hole or drain beside them which results in they simply turn to the hole and fall down. In this case, the white cane is unable to detect the side hole. In this paper, we are designed and fabricated a novel concept of a walking stick for blind people which able to detect hole to avoid falling in the hole. A laser sensor is attached with the blind stick and continuously detects the hole which we calibrated through a set of experimentations. Other two sensors are attached with the cane are also used to detect the front obstacle. Finally, the experiments are conducted to verify the function of the blind stick prototype. The proposed walking stick prototype is able to classify the height of obstacles and detect the front hole will be very helpful to the blind user.